Aplikasi Antimicrobial Susceptibility Test (AST) dalam Mendeteksi Carbapenem-Resistant Enterobacteriaceae (CRE): Sebuah Tinjauan Sistematis - Yasmin, Thania; Mashuri, Yusuf Ari; Maryani, Maryani; Susilawati, Tri Nugraha (Majalah Kedokteran Indonesia, 2023)
Introduction: Indonesia has the highest prevalence of carbapenem-resistant Enterobacteriaceae (CRE) in Asia. This shows the importance of early detection and treatment of CRE cases. This systematic review presents recent studies on the global pravelence of CRE, the use of antimicrobial susceptibility test (AST) for detecting CRE, and detection methods of carbapenemase-producing CRE (CP-CRE). Method: A systematic review was conducted on English scientific articles published in PubMed, Science Direct, and Scopus from January 2018 to February 2022. Inclusion criteria were studies that performed CRE examination on human samples and the keywords were ‘antimicrobial susceptibility test’ OR ‘microbial sensitivity test’ OR ‘antimicrobial susceptibility breakpoint determination’ AND ‘carbapenem-resistant Enterobactericeae’ OR ‘carbapenemase-producing Enterobacteriaceae’. The study selection was carried out according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA). Result: The literature search and study selection method resulted in a total of 11 articles for data extraction and analysis. The prevalence of CRE was 9.6% in the study that aimed for CRE screening. CRE is detected mostly by Vitek-2® in urine and blood samples showing imipenem and meropenem-resistant bacteria. Conclusion: The prevalence of CRE was high in the CRE case screening study. The most common CRE detection method is Vitek-2® that could be replaced with disk diffusion method in limited resources settings. CRE detection can be followed by the detection of carbapenemase-producing CRE (CP-CRE) by using genotypic, phenotypic, and fluorogenic assays.